Drought simulation on the emergence and initial growth of cotton cultivars - Fernandes, Pedro Dantas; de Azevedo, Norma César; Barros, Adilson David de (Pesquisa Agropecuaria Brasileira, 1995)
In this work, four cotton (Gossypium hirsutum, L.) cultivars, pre-soaking of seeds and two levels of soil humidity were studied in a sandy soil. The humidity levels consisted of keeping water content at field capacity until sowing, or keeping it until seedling emergence, without further irrigation. The trial was carried out in a green-house, using pots, consisting of 16 treatments, set up in a randomized block design. The experiment ended when the plants could not recover the turgidity early in the morning. They were harvested and evaluated in relation to several variables. The results showed that the CNPA-Precoce cultivar was the most resistant to water stress, with the aerial parts less developed than the other cultivars, but with greater dry matter of roots. The CNPA-Acala cultivar was the least tolerant to water deficit. Seed presoaking was more favorable to plant emergence under water stress conditions.